The Analysis Of Student's Response To The Development Of Media-Based Android On Subjects Nahwu - Moch Umar Hasan,; Sulaikho, Siti ((الطموحات ) EL-THUMUHAT, 2021)
In previous studies, researchers have been developing a learning media which is used for increasing the achievement of students on the subjects nahwu with the utilization of powerpoint and ispring suite, but researchers do not yet know how the response of the students of class VIII MTsN 3 Jombang as a research subject. This study aims to determine how the response of students after the development of interactive learning media based on android. This research uses descriptive method with data collection in the form of a closed questionnaire, calculated with the scale linkert then analyzed according to the needs of researchers. The results of the questionnaire responses of students towards learning media shows the results of percentage with very good category.